Emerging Technologies for Water Supply, Conservation and Management - Balaji, Etikala; Veeraswamy, Golla; Mannala, Prasad; Madhav, Sughosh (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book deals with the role of emerging technologies such as remote sensing and GIS and artificial intelligence/machine learning in water supply, conservation and management for sustainable development. These are low-cost new technologies that address current challenges dealing with large data sets, such as identifying spatial and temporal variations in water quality parameters and contaminants, groundwater potential zones and water supply and management issues. This book is helpful to show the paths of reducing the burden of time and cost and is the alternative options for the conventional practices in water supply, conservation and management. Further, the outcomings of this book are helpful for policy makers, researchers and readers.
Assessment of Water Consumers Literacy -- Machine learning applications in sustainable water resource management: A systematic review -- Remote Sensing and Machine Learning Applications for the Assessment of Urban Water Stress: A Review -- Role of Artificial Intelligence in Water Conservation with special reference to India -- Remote sensing and GIS based techniques for monitoring and conserving water on newly developed farmlands -- A Comprehensive Review on Mapping of Groundwater Potential Zones: Past, present and future recommendations -- Geographic Information System and Remote Sensing in deciphering groundwater potential zones -- Remote Sensing & GIS based monitoring and management of coastal aquifers and ecosystem -- Hydrogeomorphological mapping of groundwater potential zones using multi-influence factor (MIF) and GIS techniques: A case study of Vishav watershed, western Himalayas -- GIS-based disaster risk analysis of floods using certainty factor (CF) and its ensemble with deep learning neural network (DLNN): A case study of Dima Hasao district of Assam -- Geospatial and Analytical Hierarchical Techniques to assess the groundwater potential areas in Kanyakumari district, Tamil Nadu -- Application of Remote Sensing and GIS in Mapping Groundwater Potential Zones through Fuzzy Integration in Kodavanar Watershed, A part of Amaravathi Basin, Tamil Nadu -- Morphometric analysis using geospatial techniques in the Pandameru River Basin, Anantapur District, Andhra Pradesh, India -- Ground Water Quality assessment using Water Quality Index and Geographical Information System of Mogamureru River Basin, Y.S.R. District, A.P., India -- Using Geo-spatial Technologies for Land and Water Resource Development Planning: A Case Study of Tirora Tehsil, India -- Delineation of Seawater Intrusion into freshwater aquifers by using VES & GIS in the Kakinada Region, East Godavari District, Andhra Pradesh, India -- . Systematic approach of groundwater resources assessment using remote sensing and multi-influence factor (MIF) techniques in Medchal Mandal, Telangana State, India -- Remote sensing snd GIS Application for Rainwater Harvesting and Groundwater Recharge to Secure Sustainable Groundwater Future of Adikavi Nannaya University, Rajamahendravaram, India.
Keywords: Geophysics; Water; Hydrology; Environmental management; Artificial intelligence; Geophysics; Water; Environmental Management; Artificial Intelligence